Impact of ART on the fertility of HIV‐positive women in sub‐Saharan Africa. Issue 9 (22nd July 2016) - Yeatman, Sara; Eaton, Jeffrey W.; Beckles, Zosia; Benton, Lorna; Gregson, Simon; Zaba, Basia
Abstract: Objective: Understanding the fertility of HIV‐positive women is critical to estimating HIV epidemic trends from surveillance data and to planning resource needs and coverage of prevention of mother‐to‐child transmission services in sub‐Saharan Africa. In the light of the considerable scale‐up in antiretroviral therapy (ART) coverage over the last decade, we conducted a systematic review of the impact of ART on the fertility outcomes of HIV‐positive women. Methods: We searched Medline, Embase, Popline, PubMed and African Index Medicus. Studies were included if they were conducted in sub‐Saharan Africa and provided estimates of fertility outcomes (live births or pregnancies) among women on ART relative to a comparison group. Results: Of 2070 unique references, 18 published papers met all eligibility criteria. Comparisons fell into four categories: fertility of HIV‐positive women relative to HIV‐negative women; fertility of HIV‐positive women on ART compared to those not yet on ART; fertility differences by duration on ART; and temporal trends in fertility among HIV‐positive women. Evidence indicates that fertility increases after approximately the first year on ART and that while the fertility deficit of HIV‐positive women is shrinking, their fertility remains below that of HIV‐negative women. These findings, however, were based on limited data mostly during the period 2005–2010 when ART scaled up. Conclusions: Existing data are insufficient to characterise how ART has affected the fertility of HIV‐positive women in sub‐Saharan Africa. Improving evidence about fertility among women on ART is an urgent priority for planning HIV resource needs and understanding HIV epidemic trends. Alternative data sources such as antenatal clinic data, general population cohorts and population‐based surveys can be harnessed to understand the issue.